Capital Structure, Liquidity and Profitability of Chemical Industry in India - Palaniappan, A.; Velusamy, P. (Prabandhan: Indian Journal of Management, 2009)
The chemical industry is a multifaceted industry and plays a vital role in the economic development of India. The Indian chemical industry comprises both large and small units. The fiscal concessions granted to small scale sector in mid-eighties led to establishment of a large number of units in the small scale industry. Capital is a limited productive resource in developing economies and proper utilization of this resource promotes the rate of growth, cuts down the cost of production and above all improves the efficiency of the productive system. Fixed capital and working capital are the dominant contributors to the total capital of the industries. Fixed capital investment generates production capacity whereas working capital makes the utilization of the capacity possible. An attempt is made in this study to analyze the behavior of fixed and working capital of chemical industry of large public limited companies.